Biocontrol - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Worldwide, the estimated pesticide use in agriculture is 2.7 million tons (Mt) of active ingredients (FAOSTAT). Despite their accessibility and efficacy, chemical pesticides raise numerous environmental concerns. Chemical pesticides can pollute ecosystems by contaminating soil, air, and freshwater through various pathways, including volatilization [1], spray drift [2], runoff from fields [3], and improper product management [4], like improper disposal of empty containers or incorrect dosage. This contamination can have detrimental effects on aquatic ecosystems [5], harm animals [6], and pose risks to human health through contaminated drinking water sources [7]. The second major concern is the undesired impacts on biodiversity: The use of chemical pesticides is frequently linked to a decrease in populations of non-target species [8], [9], [10], and can also lead to the development of resistance by target species [11], [12], further unbalancing the equilibrium of species populations. Moreover, resistance to pesticides induces the use of alternative and often more potent chemical products, further perpetuating the cycle of environmental harm.